2021
DOI: 10.1177/2325967120982309
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Pediatric Athletes Have Significant Baseline Limb Asymmetries on Common Return-to-Sport Physical Performance Tests

Abstract: Background: Return to sport (RTS) after anterior cruciate ligament (ACL) reconstruction in children is associated with a much higher risk (∼30%) of subsequent ACL injury than in adults. Most RTS testing protocols use a limb symmetry index (LSI) ≥90% on physical performance tests (PPTs) to assess an athlete’s readiness for sport. This assumes that, in a healthy state, the physical performances across both lower extremities are and should be equal. Purpose: To determine the prevalence of limb asymmetries >10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…An LSI of >90% in the hop tests is a generally accepted goal following ACL reconstruction. However, in healthy children (6–18 years old) [26], a relatively large asymmetry between the right and left legs in hop tests has been reported (SL = 67% LSI, 6 M = 73% LSI and CO = 65% LSI) [26]. Others reported that only 75% of children 9–15 years old had an LSI above 85%, which is considered normal in healthy adults, and that only about 60% of healthy children had an LSI above 90% [4, 45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An LSI of >90% in the hop tests is a generally accepted goal following ACL reconstruction. However, in healthy children (6–18 years old) [26], a relatively large asymmetry between the right and left legs in hop tests has been reported (SL = 67% LSI, 6 M = 73% LSI and CO = 65% LSI) [26]. Others reported that only 75% of children 9–15 years old had an LSI above 85%, which is considered normal in healthy adults, and that only about 60% of healthy children had an LSI above 90% [4, 45].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of anterior cruciate ligament (ACL) injuries in children and adolescents is increasing worldwide [41,7,19,23,26]. During the last two decades, there has been a 2.3% increase per year in ACL injuries among 6-to 18-year-olds, now accounting for more than 10% of all sports-related injuries among 13-to 17-yearolds [22,29,39,40].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scores range from 0% to 100%, where 100% suggests full functional symmetry [ 35 ]. The LSI is commonly used for return-to-activity decisions with a target of 85% LSI before full return-to-activity [ 35 , 36 , 37 ], and asymmetries greater than 15% being associated with an increased injury risk [ 36 ]. In the current study, the LSI was calculated as (higher value/lower value) × 100 across legs at two time points: freshman and senior scores [ 38 ].…”
Section: Methodsmentioning
confidence: 99%